2018
DOI: 10.1016/j.ausmj.2018.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Value of a Peer-To-Peer Mentoring Experience

Abstract: Globalization of business skills has become critical as employers have a requirement for culturally adaptable marketing and business graduates who are “work ready” in either Australia or overseas. These students must have both discipline knowledge and soft skills including cultural competence. How students develop intercultural skills at university is discussed. Given that more than ninety percent of local university students do not participate in academic offshore experiences, a focus is on the internationali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 69 publications
(96 reference statements)
0
10
0
1
Order By: Relevance
“…Unlike in the cases of Abegglen, Burns, and Sinfield [5]; Ragavan [16]; Cropper [18], the mentors and mentees in the current study came from similar locale, familiar with each other, and all of them were peers although the mentors were senior university students while the mentees were junior university students who were majoring in biological science. It was claimed that a mentoring program that falls in the same clout, culture, and specific experience (in the case of the mentor) is most likely to succeed [18], [19]. Moreover, unlike in the cases of Abegglen, Burns, and Sinfield [5]; Ragavan [16]; Cropper [18], the current study needed not to take more time to establish relationships as they belong to the same college and mostly, they were friends.…”
Section: Nature Of the Little Teachers 311 Accommodating Mentormentioning
confidence: 99%
“…Unlike in the cases of Abegglen, Burns, and Sinfield [5]; Ragavan [16]; Cropper [18], the mentors and mentees in the current study came from similar locale, familiar with each other, and all of them were peers although the mentors were senior university students while the mentees were junior university students who were majoring in biological science. It was claimed that a mentoring program that falls in the same clout, culture, and specific experience (in the case of the mentor) is most likely to succeed [18], [19]. Moreover, unlike in the cases of Abegglen, Burns, and Sinfield [5]; Ragavan [16]; Cropper [18], the current study needed not to take more time to establish relationships as they belong to the same college and mostly, they were friends.…”
Section: Nature Of the Little Teachers 311 Accommodating Mentormentioning
confidence: 99%
“…However, the majority of university students do not participate in international exchange programmes, hence "internationalization-at-home" activities remain an important opportunity for skill development [17]. Griffiths et al [17] (ibid.…”
Section: Good Practices Of Cross-cultural Learningmentioning
confidence: 99%
“…However, the majority of university students do not participate in international exchange programmes, hence "internationalization-at-home" activities remain an important opportunity for skill development [17]. Griffiths et al [17] (ibid. ), using a quasiexperimental pre-and post-test survey, concluded that these activities can have a significant effect on a range of cultural competences.…”
Section: Good Practices Of Cross-cultural Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…Contemporary literature reports on many ‘alternative’ forms of mentoring such as peer mentoring, group mentoring, e‐mentoring, co‐mentoring or collaborative mentoring, multiple‐level mentoring, and reverse mentoring (where a younger, junior employee mentors an older, senior colleague to share their technological expertise and generational perspective) (Ensher, Heun and Blanchard 2003; Griffiths, Kopanidis and Steel 2018; Mullen 2016; Murphy 2012; Pololi and Evans 2015). These different forms of mentoring can generally be categorised as either ‘informal’ or ‘formal’.…”
Section: Informal and Formal Mentoringmentioning
confidence: 99%